Congenital adrenal hyperplasia–a clinical and genetic survey. Are we detecting male salt-losers?. Issue 8 (August 1980) - Murtaza, L; Sibert, J R; Hughes, I; Balfour, I C
Abstract : In a genetic and clinical study in Wales of congenital adrenal hyperplasia due to 21-hydroxylase deficiency, 26 cases were found in the period 1966 to 1977. No one was known to have died from the condition in the period. There were 14 female and 5 male salt-losers, and 5 female and 2 male nonsalt-losers. The discrepancy between the sexes suggests that some cases of congenital adrenal hyperplasia in males are not being detected. This is of concern as salt-losing cases may be dying without a diagnosis being established. The carrier incidence of the condition in females, assuming complete ascertainment, is 1:55. Salt-losers in Wales appear to be more than twice as common as nonsalt-losers. HLA typing of certain affected families confirmed a genetic linkage between the congenital adrenal hyperplasia gene and HLA. This linkage appears to exist in both forms of congenital adrenal hyperplasia and suggests that the genes for salt-losing and nonsalt-losing forms of congenital adrenal hyperplasia are alleles. The linkage between congenital adrenal hyperplasia and HLA provides a potential method for antenatal detection. However, only a few parents would wish to take advantage of this method if it were readily available.